Talent identification of young players in a professional soccer club - Gil, S. M.; Zabala-Lili, J.; Bidaurrazaga-Letona, I.; Badiola, A.; Santos Concejero, J.; Lekue, J. A.; Granados, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Selecting the most talented young players is essential for high-level soccer clubs (1). Thus, the aim of the study was to analyse the talent identification process of soccer players selected to be incorporated to the youngest team of a professional club. Methods: The selection was performed by the technical staff of the Athletic Club of Bilbao through the observation of players (aged 9-10 years) during training sessions and matches. This process had two phases: firstly, identification (pre-selection) of the best players of the county (54 outfield players, OFs, and 10 goalkeepers) and a final selection (17 OFs and 4 goalkeepers). Also, these groups were compared to 34 aged-matched non-(pre)selected players of an open soccer camp (Camp). Pre-selected and Camp players underwent anthropometric, maturity and performance (30-m sprint, 30-m+10cones, Yo-Yo IR level1, CMJ, hand-dynamometry) measurements at the beginning of the study. Statistical comparisons, using student`s t or U-Mann-Whitney`s tests, were made once the final selection was performed. Results: Pre-selected OFs were older (9.83±0.27 vs. 9.63±0.29 years, p<0.05) and leaner (sum of skinfolds: 48.86±15.50 vs. 66.16±29.75 mm,p<0.05) than Camp players. Besides, they performed better in velocity (4.96±0.21 vs. 5.53±0.30 s, p<0.001), agility (5.81±0.28 vs. 6.38±0.32 s, p<0.001), endurance (617.95±233.24 vs. 463.52±223.27 m, p<0.01) and CMJ (29.07±3.27 vs. 26.87±3.07 cm, p<0.01). OFs who were finally selected were older (9.95±0.29 vs. 9.78±0.25 years, p<0.05) and displayed better agility (5.68±0.27 vs. 5.86±0.27 s, p<0.05) and endurance (725.71±226.73 vs. 574.85±224.62 m, p<0.05) than the non-finally-selected OFs. Regarding goalkeepers, they were taller, heavier and had more body fat than OFs; also, they performed worse in the physical tests (p<0.05). Finally selected goalkeepers were older, taller, had a taller predicted height, advanced maturity and performed better in the hand dynamometry and jump tests (p<0.05) than the non-finally-selected. Discussion: Thus, the technical staff selected OFs with a particular anthropometry and the best performance, particularly agility and endurance, while goalkeepers had a different profile. Moreover, chronological age had an important role in the whole selection process (2).